2010
DOI: 10.1021/tx900417f
|View full text |Cite
|
Sign up to set email alerts
|

Integrated in Silico−in Vitro Strategy for Addressing Cytochrome P450 3A4 Time-Dependent Inhibition

Abstract: Throughout the past decade, the expectations from the regulatory agencies for safety, drug-drug interactions (DDIs), pharmacokinetic, and disposition characterization of new chemical entities (NCEs) by pharmaceutical companies seeking registration have increased. DDIs are frequently assessed using in silico, in vitro, and in vivo methodologies. However, a key gap in this screening paradigm is a full structural understanding of time-dependent inhibition (TDI) on the cytochrome P450 systems, particularly P450 3A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 56 publications
0
45
0
Order By: Relevance
“…Where A is the classification of model, B is the observed value, P(A) is the prior probability or marginal probability of classification A without considering any B factors, P(B) is the prior or marginal probability of the value, P(B|A) is the posterior probability (the probability of value B if classification A is true), and P(A|B) is the probability that classification A is true given the observed data B (also called the posterior probability) [22] .…”
Section: Modeling Methodsmentioning
confidence: 99%
“…Where A is the classification of model, B is the observed value, P(A) is the prior probability or marginal probability of classification A without considering any B factors, P(B) is the prior or marginal probability of the value, P(B|A) is the posterior probability (the probability of value B if classification A is true), and P(A|B) is the probability that classification A is true given the observed data B (also called the posterior probability) [22] .…”
Section: Modeling Methodsmentioning
confidence: 99%
“…A visualization of the chemical space covered by a test and training set can be created using principal component analysis (PCA) (Zientek et al, 2010). Such a visual chemical space map was generated for the HLM dataset by converting the CDK and SMARTS descriptors (total ϳ579 descriptors) into principal components (PCs).…”
Section: Methodsmentioning
confidence: 99%
“…This process would allow significant cost savings by not screening each compound. A recent study by us suggested an approximately 30% saving in in vitro testing by implementing computational models (Zientek et al, 2010). Clearly, we should also be cognizant of the chemical space coverage of the model.…”
Section: Downloaded Frommentioning
confidence: 99%
“…We have previously found the related technique principal components analysis useful in understanding how individual probe substrates report on different regions of the functional space of single P450 isoforms (Nath and Atkins, 2008b) and also in the prediction of a compound's propensity to cause time-dependent inhibition of CYP3A4 (Zientek et al, 2010). In this study, we extend this approach from considering multiple probe substrates of a single enzyme to a panel of different enzymes, with the goal of understanding how P450s are distributed in functional space with respect to their susceptibility toward inhibition.…”
Section: Introductionmentioning
confidence: 99%